Radioimmunotherapy of lymphoma - Goldsmith Stanley J. (Archive of Oncology, 2012)
Radiolabeled monoclonal antibodies for the treatment of follicular low-grade non-Hodgkin’s lymphoma have been available for several years in the United States and more recently throughout Europe. Since their introduction to treatment of refractory or relapsed patients, they have been evaluated for efficacy earlier in the course of the disease including so-called 1st line therapy in conjunction with initial chemotherapy and as consolidation therapy in patients who have achieved remission following a course of chemotherapy. It can be expected that these agents will become more widely available. Two agents are currently distributed commercially: Bexxar® consisting of 131I-labeled tositumomab and cold (unlabeled) tositumomab and Zevalin® consisting of 90Y-labeled Ibritumomab and cold rituximab. All 3 antibodies recognize a cell surface antigen, CD20, found on normal and malignant B lymphocytes characteristic of follicular lymphoma. The nomenclature: ”…tumomab” indicates that it is a tumor murine monoclonal antibody while “…ximab” indicates that it is a chimeric molecule in which a portion of the murine IgG has been removed and replaced with an equivalent component of human IgG. Rituximab is available in many countries for use as an immunotherapeutic either alone in relapsed patients or in conjunction with standard chemotherapeutic regimen. Because of the limited access to the radiolabeled products in Australia, Harvey Turner and colleagues in Perth radioiodinated rituxan (the nonradioactive component of Zevalin®), developed a protocol similar to Bexxar® and obtained gratifyingly similar good results. Clinical use depends upon evidence of CD20 expression (usually available from biopsy material at diagnosis), confirmation of less than 25% of marrow involvement, platelet counts >100,000 and preferably 150,000 and granulocyte count > 3500. For either product, dosing is based on platelet count and body weight [up to 137% ideal weight). Zevalin® dosage is 15 MBq (0.4 mCi)/kg if platelets exceed 150K; 11 MBq (0.3 mCi)/kg between 100K-150K. Bexxar® administration is based on whole body radiation absorbed dose determined by measuring whole body counts on 3 occasions after administration of 185 MBq (5 mCi) of the 131I-tositumomab. In all instances, cold antibody is infused prior to the labeled component. In early studies, 67-80% of the patients achieved a partial or complete response of greater duration than in their prior treatment. More recently, when used as the 1st line or consolidation therapy, near 100% overall response rates have been observed.